Human resource management casebook - Bruce, Peter J (Pearson Education Australia, 2007)
This practical resource for use in academic teaching environments will enable students to apply theoretical concepts through the use of two approaches to case study analysis. P Bruce, Swinburne University, Sydney. & A McCall, Victoria University.